From Petri Dishes to Organ on Chip Platform: The Increasing Importance of Machine Learning and Image Analysis - Mencattini, Arianna; Mattei, Fabrizio; Schiavoni, Giovanna; Gerardino, Annamaria; Businaro, Luca; Di Natale, Corrado; Martinelli, Eugenio (Frontiers in Pharmacology, 2019)
The increasing interest for microfluidic devices in medicine and biology has opened the way to new time-lapse microscopy era where the amount of images and their acquisition time will become crucial. In this optic, new data analysis algorithms have to be developed in order to extract novel features of cell behavior​ and cell-cell interactions. In this brief article, we emphasize the potential strength of a new paradigm arising in the integration of microfluidic devices (i.e., organ on chip), time-lapse microscopy analysis, and machine learning approaches. Some snapshots of previous case studies in the context of immunotherapy are included as proof of concepts of the proposed strategies while a visionary description concludes the work foreseeing future research and applicative scenarios.